Cytotoxic Flavonoid from Achillea talagonica Bioss. - S Saeidnia; F Moradi-Afrapoli; AR Gohari; M Malmir (Institue of Medicinal Plants, ACECR, 2009)
Background: Achillea talagonica (Asteraceae) is an endemic herbaceous plant in Iran with small yellow flowers and several times pinnately divided leaves in worm shape. The plant was found to be cytotoxic in our previous studies.   Materials and Methods: A. talagonica was collected in May 2005 from Talegan in north of Iran during the full flowering stage. Dried aerial parts of the plant were reduced in to small pieces and percolated with ethyl acetate for 72 hours. The extract obtained was filtered and then concentrated under reduced pressure and completely dried by a freeze dryer. Column chromatography of the extract on silica gel and sephadex LH-20 yielded in isolation of three main components. Cytotoxic activity was evaluated against the Artemia salina larvae by the Brine Shrimp Cytotoxicity Bioassay.   Results: Isolated compounds were identified as β-sitosterol (1), salvigenin (5- hydroxy 4chr('39'), 6, 7- three methoxy flavone) (2) and santoflavon (5- hydroxy 4chr('39'), 3chr('39'), 6, 7- tetra methoxy flavone) (3). NMR data of all the isolated compounds showed good agreement with literature data. Conclusions: In our previous studies ethyl acetate extract of A. talagonica showed cytotoxic activity in brine shrimp lethality assay. The results of BST assay indicated that only santoflavone (3) showed a good cytotoxic activity (LC50 = 15 μ g/ml) against A. salina larvae so this compound seems to be responsible for the extract toxicity of A. talagonica against Artemia nauplii.